Postpartum Experiences of Early Skin-to-Skin Contact and the Traditional Separation Approach After a Very Preterm Birth: A Qualitative Study Among Mothers - Anne Marit Føreland; Helene Engesland; Laila Kristoffersen; Liv Fegran (Global Qualitative Nursing Research, 2022)
Traditional care immediately after very preterm birth separates the mother and child by the transfer of the infant to the neonatal intensive care unit. A nonseparation approach is currently being considered, allowing early skin-to-skin contact in the delivery room/postoperative care unit. This study aimed to explore mothers’ experiences of early skin-to-skin contact and traditional care. A qualitative study using individual semi-structured interviews with five mothers from each of the two groups was conducted. Content analysis revealed that both groups’ experiences were characterized by (i) mothers’ need to be affirmed of their infants’ vitality, (ii) bonding challenges, and (iii) benefits of skin-to-skin contact. We suggest that early skin-to-skin contact after very preterm births is crucial for the bonding process and mothers’ feelings of safety and well-being. When early skin-to-skin contact is infeasible, our findings reveal the significance of photos, information, and the father’s presence at the time of postpartum separation.